Accurate charge transport model for nanoionic memristive devices. (July 2017) - Amirsoleimani, Amirali; Shamsi, Jafar; Ahmadi, Majid; Ahmadi, Arash; Alirezaee, Shahpour; Mohammadi, Karim; Karami, Mohammad Azim; Yakopcic, Chris; Kavehei, Omid; Al-Sarawi, Said
Abstract: Memristors have the potential to significantly impact the memory market, and have demonstrated the potential for analog computing within a sub-class of neuro-inspired information processing. In order to enable circuit designers to use and test memristor/CMOS hybrid circuits, it is necessary to have an accurate and reliable memristor model. In this work, a new memristor model based on Charge Transport Mechanism (CTM) is presented. This paper analyzes different current mechanisms that exist in Schottky barrier region of memristors: direct tunneling, thermionic emission, and Ohmic currents. The proposed memristor model is based on direct tunneling and Ohmic conduction, and it accounts for physical phenomena within memristive devices. The presented model shows a relative root mean square error of about 0.25 when compared with experimental results for a Ag/TiO2 /ITO memristor. It also shows better accuracy in comparison with other modeling approaches published in the literature. The proposed model is implemented in SPICE and a subcircuit for the model is provided.